Effectiveness of Radio Sengerema’s Publice service announcement in Promoting Voter Education During the 2024 Local Government Election in Sengerema, Tanzania - Devotha Mvungi; Peter C. Mataba (Technium Social Sciences Journal, 2026)
Voter education is a critical element in strengthening democratic participation and accountability at the local level. This study examined the effectiveness of Radio Sengerema’s public service announcements (PSAs) in promoting voter education during the 2024 Local Government Election in Sengerema, Tanzania. Guided by agenda-setting theory, the research employed a descriptive survey design supplemented by qualitative in-depth interviews. A purposive sample of fourteen community members including local leaders, radio staff, and voters was selected to provide detailed insights into PSA effectiveness. Findings revealed that the PSAs significantly enhanced voters’ knowledge of electoral procedures, responsibilities, and civic engagement. Message repetition reinforced retention and motivation to participate, while timing and clarity of announcements influenced accessibility. The study recommends that community radio stations design culturally relevant and frequent PSAs, electoral authorities collaborate more closely with media outlets, and civil society organisations support voter sensitisation initiatives. This research contributes to knowledge by demonstrating the role of local radio as an effective platform for voter education in Tanzanian local government elections.